THE PRESENCE OF ANTIOXIDANTS IN THE HAIR INFUNDIBULUM IMPLICATIONS IN HAIR DISEASES SUCH AS ALOPECIA - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2022)
Anatomically, as a rule the hairs in mammals consists of an unseen follicle or root anchored into the skin with a shaft or visible hair exiting exteriorly. As a note of interest, the hair follicle has been described as a miniorgan having its own cells division, metabolism and aging stages (1). As previously stated “metabolism entails electron transfers in both plants (photosynthesis) and animals (cellular respiration) involving movement of electrons from donor to acceptor along the electron transfer chain thus inducing a current within each cell and from cell to cell” (2,3). This continuity of energy transfer in living organisms is at the very essence of life; and is ubiquitously present in all living matter and the generator of Bioelectricity (a.k.a. electromagnetic radiation), the protein enzyme catalase having an essential pivotal role in energy production in the breakdown of toxic materials such as H2O2 into H2O and O2 molecules. During the breakdown of O2 molecules energy is generated. When catalase is depleted life ends and regional death occurs (4,5). We could then theorize that if cell respiration ceases throughout the entire organism (organs) death ensues (6). Only in living tissue is that elimination of toxic material such as H2O2 has any relevance.